2013
DOI: 10.1167/iovs.12-10469
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-A Irradiation Upregulated Urokinase-Type Plasminogen Activator in Pterygium Fibroblasts through ERK and JNK Pathways

Abstract: UVA stimulated the production of uPA, a key factor in the modulation of extracellular matrixes, inflammatory processes, and angiogenesis. This may have a role in the development and progression of pterygium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 52 publications
1
34
0
1
Order By: Relevance
“…69 Recently, Chao et al reported mRNA levels and activity of the urokinase-type plasminogen activator (uPA) in pterygium fibroblasts after UV-A radiation. 70 This protease can activate matrix metalloproteinases (MMPs) and is responsible for tissue degradation and tumor cell invasion. 71,72 Among the studies conducted with pterygium cells, both epithelial and stromal fibroblasts have been shown to express molecules related to connective tissue degradation and remodeling of MMP-1 and MMP-2, [73][74][75] suggesting that both cell types may contribute to the dissolution of the basement membrane and the Bowman layer.…”
Section: Causative Factors Uv Radiationmentioning
confidence: 99%
“…69 Recently, Chao et al reported mRNA levels and activity of the urokinase-type plasminogen activator (uPA) in pterygium fibroblasts after UV-A radiation. 70 This protease can activate matrix metalloproteinases (MMPs) and is responsible for tissue degradation and tumor cell invasion. 71,72 Among the studies conducted with pterygium cells, both epithelial and stromal fibroblasts have been shown to express molecules related to connective tissue degradation and remodeling of MMP-1 and MMP-2, [73][74][75] suggesting that both cell types may contribute to the dissolution of the basement membrane and the Bowman layer.…”
Section: Causative Factors Uv Radiationmentioning
confidence: 99%
“…In this graph, the y axis represents the threshold value for damage to occur. In vivo responses to overexposure to UV radiation (Chao et al, 2013) include haze in the epithelium and stroma, discharge and debris in the tears, and granules in the endothelium.…”
Section: Corneamentioning
confidence: 99%
“…The primary response is in the corneal epithelium, but effects can penetrate beyond Bowman's membrane to the stroma (Cullen, 2002). Pterygium is a chronic response to UV radiation exposure (Chao et al, 2013). It is an inflammatory, proliferative growth on the cornea and conjunctiva that can impair vision.…”
Section: Corneamentioning
confidence: 99%
See 1 more Smart Citation
“…3 All these risk factors including the exposure to ultraviolet light may contribute to the development of pinguecula and pterygium. 4 The presence of pinguecula or pterygium is an incidental finding during routine eye examination or it may be noticed by self/relatives/friends at times. Many people seek consultation because it results in not only cosmetic blemish and it may extend on to the corneal surface and result in irregular astigmatism and visual impairment.…”
Section: Introductionmentioning
confidence: 99%